Deep sequencing microRNA profiles associated with wooden breast in commercial broilers - Jingting Shu (Elsevier, 2021)
ABSTRACT: Wooden breast (WB) is a muscle disorder affecting modern commercial broiler chickens that leads to a palpable firm pectoralis major muscle and causes severe reduction in meat quality, resulting in substantial economic losses for the poultry industry. Most studies have focused on the regulatory mechanisms underlying this defect with respect to the gene and protein expression levels as well as the levels of metabolites. MicroRNAs (miRNAs) play critical roles in human muscular disorders, such as the Duchenne muscular dystrophy, by regulating the muscle regeneration or fibrosis processes. In this study, we investigated the miRNAs and related pathways that play important roles in the development of WB. We generated the miRNA expression profiles of the pectoralis major muscle samples from 3 WB-affected and 3 nonaffected chickens selected from a commercial broiler population via small RNA sequencing. A total of 578 miRNAs were identified in the chicken breast muscles from the initial analysis of the sequencing data. Of these, 23 miRNAs were significantly differentially expressed (false discovery rate [FDR] <0.05, log2|Foldchange| >1), including 20 upregulated and 3 downregulated miRNAs in the WB group compared to the normal group. Moreover, functional enrichment of the predicted target genes of differential miRNAs indicated that these miRNAs were involved in biological processes and pathways related to energy metabolism, apoptosis, focal adhesion, and development of blood vessels. Four differentially expressed miRNAs were validated by quantitative real-time polymerase chain reaction (qRT-PCR). We also highlighted several differentially expressed miRNAs, such as gga-miR-155, gga-miR-29c, and gga-miR-133, for their potential roles in the regulation of the development of WB. To the best of our knowledge, this is the first study investigating the miRNA expression profile of the breast muscle associated with WB. The findings of this study can be used to explore the potential molecular mechanisms of other muscle disorders in broilers and provide valuable information for chicken breeding.